In vitro and In vivo neuroprotective study of solid lipid nanoparticles loaded with dimethyl fumarate - Ojha, Smriti (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Dimethyl fumarate (DMF) is a FDA approved oral medication used to treat patients with multiple sclerosis (MS). Biological half-life of DMF is about 1 h, and it is rapidly hydrolyzed to its active metabolite monomethyl fumarate. The objective of present study is to formulate and characterize DMF loaded solid lipid nanoparticles (SLNs) to overcome these limitations. Material and Methods: DMF loaded SLNs were prepared by hot microemulsion and sonication method. Stearic acid was used as lipid and soy lecithin was colipid. Results and Discussion: The synthesized SLNs offered an average particle size of 300 nm, polydispersity index <0.3, and zeta potential value of âˆ’34.89 mv. In vitro evaluation on human neuroblastoma SH-SY5Y cells confirmed to have a neuroprotective effect of these colloidal systems under oxidative stress. DMF loaded SLNs showed to increase cell viability under H2O2 induced cell apoptosis. Cuprizone mouse model for MS was used to evaluate the effect of DMF loaded SLNs on locomotion score. Conclusion: In vitro study also confirmed a better locomotion and motor coordination scores in cuprizone mouse model for MS.